Economic development and regional cooperation : Kuwait - El Mallakh, Ragaei; Polk, William R. (Chicago : University of Chicago Press, 1968)
A detailed account of Kuwaits role as a donor of foreign aid covering topics like: an introduction to the economics of rapid development; the economics of oil; financing domestic development; balanced growth and planning; regional economic cooperation: motive, patterns and shortcomings; foreign aid: a new factor; and maintaining development: summing up.
Includes index.
Includes bibliographical references: p. 240-245.
lje 28/09/2018
Loans
Keywords: Economic history; International economic relations; Economic policy; Economic development; Regional economics; Economic assistance, Kuwait; Kuwait; Arab countries